The Ethnolinguistic Worldview and its Reflection in Russian and Uzbek Folklore (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the ethnolinguistic worldview as a reflection of national consciousness in linguistic and cultural practices, with an emphasis on Russian and Uzbek folklore. The author analyzes the features of the conceptualization of space, nature, human personality and social norms enshrined in the folklore texts of both peoples. The comparison of folklore genres, symbols and the figurative system makes it possible to identify both common universals and culturally specific elements of ethnolinguistic thinking. The conclusion is made about the deep connection of language and folklore with national mentality, as well as the role of folklore in the preservation and transmission of ethnocultural values.